Influence Of Triu-B, Ovsynch And Heatsynch Protocols On Estrus Induction Response, Conception And Biochemical And Minerals Profile In Anoestrus Crossbred Cows - Buhecha, K.V.; Dhami, A.J.; Hadiya, K.K.; Parmar, C.P.; Parmar, S.C.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was planned to evaluate the fertility response and plasma profile of biochemical and mineral constituents in 46 postpartum anoestrus crossbred cows (>90 days) treated with different standard hormonal protocols (TriU-B/PRID, Ovsynch and Heatsynch, n=12 each), keeping untreated anoestrus control (n=10) and normal cyclic control (n=10) groups. All the cows (100 %) under TriU B, Ovsynch and Heatsynch protocols exhibited induced estrus within mean intervals of 67.00±1.74, 69.83±0.87 and 68.17±1.24 h, respectively, from PGF2α injection, with prominent to moderate estrus signs. The conception rates obtained at induced estrus in cows under TriU-B, Ovsynch and Heatsynch protocols were 33.33, 41.66 and 33.33 per cent, respectively. The corresponding overall conception rates of three cycles were 50.00, 58.33 and 41.66 per cent, respectively. In anoestrus animals under TriU-B, Ovsynch and Heatsynch protocols, and in normal cyclic control group, the overall pooled mean plasma total cholesterol concentrations found were 218.32±5.81, 218.65±6.04, 202.44 ±5.73 and 225.87±9.09 mg/dl (P
Keywords: Anoestrus; Blood profile; Crossbred cows; Estrus synchronization; Ovsynch; Heatsynch; PRID